Non-NMDA receptor-mediated neurotoxicity in cortical culture - Koh, JY (J Neurosci, 1990)
The neurotoxicity of 3 non-NMDA glutamate receptor agonists--kainate, alpha-amino-3-hydroxy-5-methyl-4-isoxazole-propionate (AMPA), and quisqualate--was investigated quantitatively in dissociated murine cortical cultures. Five minute exposure to 500 microM kainate, but not AMPA, produced widespread acute neuronal swelling. Kainate-induced swelling was resistant to 2-amino-5-phosphonovalerate (APV) or replacement of extracellular sodium with choline but attenuated by either kynurenate or low concentrations of quisqualate. Unlike NMDA agonists, kainate or AMPA did not produce much late neuronal loss after a 5 min exposure. In contrast, 5 min exposure to 500 microM quisqualate produced both acute neuronal swelling and widespread late neuronal degeneration. This acute swelling was blocked by APV or by replacement of extracellular sodium by choline, consistent with mediation by NMDA receptors; we speculate that high concentrations of quisqualate may directly activate NMDA receptors or induce the release of endogenous glutamate. Quisqualate-induced late neuronal degeneration may be due to another unexpected process: cellular quisqualate uptake and delayed release, converting brief addition into prolonged exposure. Hours after thorough washout of exogenously added quisqualate, micromolar concentrations could be detected in the bathing medium by high performance liquid chromatography. With lengthy exposure (20–24 hr), all 3 non-NMDA agonists were potent neurotoxins, able to destroy neurons with EC50's of about 20 microM for kainate, 4 microM for AMPA, and 1 microM for quisqualate. Kynurenate and 6-cyano-7-nitroquinoxaline- 2,3-dione (CNQX), but not APV or L-glutamate diethyl ester, were effective in attenuating the neuronal degeneration induced by these agonists. CNQX was about 3 times more selective than kynurenate against kainate-induced neuronal injury, but CNQX was still nearly equipotent with APV against NMDA-induced injury. Gamma-D-glutamylaminomethyl sulfonate exhibited partial antagonist specificity for AMPA-induced toxicity.